First Report of Calonectria montana Causing Leaf Spot on Ligularia fischeri in China - Guan, Yiming (Plant disease, 2023)
Ligularia fischeri (Ledeb.) is a perennial herbal plant of Compositae that is cultivated commercially in China as a medicinal, ornamental, and edible plant. Leaf spots were observed in 2-year-old L. fischeri in Benxi County of northeast China, in August 2021. Irregular reddish brown spots ranging from 3 to 11 mm were observed on infected leaves, and each leaf had dozens of spots (Fig. 1). As the disease progressed, the diseased spots withered and the centers fell out, and multiple lesions merge into large diseased spots, causing leaf wilting. The roots and stem bases were not infected during the reproductive stage. More than 37% of the plants in a 18 ha field were infected in 2021. The ten diseased leaves were collected and cut into small (3-5 mm) pieces, which were surface-disinfested by immersing into 1% NaOCl for 2 min and rinsing with sterile distilled water three times. The leaf pieces were then placed on acidified potato dextrose agar (PDA) in petri plates and incubated in the dark at 25°C. Twenty isolates with the same morphological characteristics were obtained. Isolates were further purified by starting a new colony for each isolate from a single spore collected from water agar. Isolate TYTW7 was randomly selected for identification and pathogenicity testing. It grew rapidly and produced profuse aerial mycelia with a carmine red underside. The conidiophores had many fertile branches and formed an elongated stipe with a sphaeropedunculate vesicle at the tip. The one-septate conidia were cylindrical and almost straight with parallel walls and rounded ends. Their sizes ranged from 30.35 to 51.76 × 2.93 to 5.01 μm (n = 100) and the pathogens were initially identified as Calonectria sp. (Crous 2002; Crous et al. 2004; Lombard et al. 2015, 2016). Further confirmation of the identification was determined according to published method (Liu and Chen 2017; Shao and Li 2021). The partial gene regions including the translation elongation factor 1-alpha (GenBank accession no. OP290551), histone H3 (OP290552), calmodulin (OP290553) and β-tubulin (OP290554) were obtained, and BLAST searches showed 99-100% homology with the ex-type culture CERC 8952 (MF527049, MF527065, MF527081 and MF527107) and phylogenetic analysis combining all loci revealed that the isolate TYTW7 and the type strain of Ca. montana clustered in one group (Fig. 2). Based on morphological characteristics and phylogenetic analysis, isolate TYTW7 was identified as Ca. Montana. Healthy 2-year-old plants were used for the pathogenicity test. A spore suspension (1×105 spores/mL water) was used to inoculate three host plants; sterile water was sprayed on the same number plants serving as a control. The experiment was repeated three times. All plants were incubated at 27±2°C (12h photoperiod) and were evaluated after seven days. The inoculated plants showed lesions on the leaf surface, similar to those in the field, and the control remained symptomless. The pathogens were successfully reisolated and identified by sequencing, and no pathogens were isolated from symptomless control plants. To our knowledge, this is the first report of Ca. montana causing L. fischeri leaf spot. The disease poses a threat to the production and more control strategies are needed on management options to minimize losses